Vibration control characteristics of a hybrid mass damper system installed in tall buildings. - Saito, Tomoo (Earthquake engineering & structural dynamics.)
A large scale hybrid mass damper (HMD) system was developed to reduce building response during strong winds and earthquakes of up to medium strength. The HMD consists of an auxiliary mass supported by multi-stage rubber bearings and actuators driven by C servomotors. Two HMDs were installed on the top floor of a target building to suppress both translational and torsional vibration. The system was installed in two high rise buildings. One was a 50 storey, 200 m high, steel frame building. The dynamic characteristics of both the building and the HMDs were identified through forced vibration tests using the HMD system. The effectiveness of the HMD system was confirmed by these tests and both wind and earthquake observation data. The other building was a triangular plan, 43 storey, steel frame building. The dynamic characteristics of the building were estimated using two different methods. One method comprised a series of vibration tests using the HMDs to excite the building. The other method was an analysis of the earthquake response records of the building, which showed the additional damping effect of the HMD system. The performance of the HMD system during a strong typhoon was also analysed.